Pertumbuhan dan status eksploitasi ikan sembilang (Plotosus canius) di perairan Kota Tanjung Pinang, Kepulauan Riau, Indonesia - Rouli Verawati Gurning; Susiana Susiana; Ani Suryanti (Akuatikisle: Jurnal Akuakultur, Pesisir dan Pulau-Pulau Kecil, 2019)
Research on the growth and exploitation status of indian catfish (Plotosus canius) is important in supporting the management of fish resources in the waters of Tanjungpinang City, Riau Islands. The study aims to determine the pattern of growth, growth parameters, and the status of indian catfish exploitation in the waters of Tanjungpinang City, Riau Islands Province. The study was conducted with a purposive sampling method of 3 stations with a total sample of 529 individual fish crosses. Analysis of growth and exploitation status data using FISAT II software and regression analysis using Excel 2017. This study resulted in a pattern of long relations and the weight of fish as a female and males both are negative allometric (faster increase in length than weight increase). The highest rate of exploitation of indian catfish is obtained from the data of 0.73 per year. This exploit value exceeds the optimum exploitation value of 0.5.